2019
DOI: 10.17478/jegys.616947
|View full text |Cite
|
Sign up to set email alerts
|

Using Technology in Hydrocarbon Topics: A Profile on Students’ Self-Regulated Learning

Abstract: This research aimed to analyse the use of chemistry-on-android (chemondro) game and blended learning that combine the online and face-to-face learning, as the implementation of technology on hydrocarbon topics toward students' selfregulated learning. The online phase of blended learning was conducted using video conference and Learning Management System (LMS). A comparative study has employed in this research. There were three groups of students with a total of 143 students represents from all of the eleventh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The chemondro-game in this research consists of learning outcomes, learning materials, and evaluation that employs game rules. Further, the chemondro-game belongs to an educational game that is found in the android mobile and accessible to the students, hence it promotes students' to learn independently and has an influence on increasing of students' self-regulated learning (Wiyarsi et al, 2019). The result of this research is confirmed by Jabbour (2014) as mobile game technology has a positive effect on the interactions between students and their peers and their teacher thus it signified on the enhancement of students' learning outcomes.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The chemondro-game in this research consists of learning outcomes, learning materials, and evaluation that employs game rules. Further, the chemondro-game belongs to an educational game that is found in the android mobile and accessible to the students, hence it promotes students' to learn independently and has an influence on increasing of students' self-regulated learning (Wiyarsi et al, 2019). The result of this research is confirmed by Jabbour (2014) as mobile game technology has a positive effect on the interactions between students and their peers and their teacher thus it signified on the enhancement of students' learning outcomes.…”
Section: Discussionmentioning
confidence: 59%
“…As in chemistry learning, teachers could be designing chemistry learning activities in such a way to yield an innovative chemistry learning by employing ICT. Various studies had implemented technologies in their activities such as innovative web learning (Thohir et al, 2020), laboratory integrated technology (Imaduddin & Hidayah, 2019), blended learning (Wiyarsi et al, 2019), interactive whiteboards (Anatürk-Tombak & Ateşkan, 2019), and android based application for chemistry learning (Ulfa et al, 2017) to improve students' chemical academic performance. Although the use of technologies may be beneficial especially in providing new information and knowledge, it offers disadvantages such hurting concentration of the students and consuming significant amounts of time (Shatri, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It should be promising since the ViChem-Lab provides effective interactive media as a supplement or replacement for the chemistry laboratory work in the learning instruction. Moreover, the presence of blended online learning gives extra learning time and learning material for students that makes a flexible learning instruction were held (Fitriyana et al, 2021;Wiyarsi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One of them is impacting the education system. the educational system is currently moving forward in the use of technology in learning [2]. On the other hand, education is required to produce humans who can adapt to the challenges of the times.…”
Section: Introductionmentioning
confidence: 99%